Habitação de interesse social: avaliação pós-ocupação no Programa Minha Casa Minha Vida - Abrahão, Soraya Caroline (2017)
Housing as an urban constitutional right should ensure access to infrastructure, transportation, public services, work and leisure. However, the reality of the most deprived population groups presents high indices of urban and housing precariousness, distancing themselves from the assured rights. Currently, the Minha Casa Minha Vida Program stands out for its attempt to eradicate the deficit, producing mass housing. The present research investigates the quality of housing produced by the program, through post-occupation evaluation in housing complexes in the municipality of União da Vitória - PR. The municipality with representative participation in its region received between 2012-2013, 624 new single-family homes through the Minha Casa Minha Vida Program, aimed at low-income families. The units constructed are divided into three sets, where two of them were built simultaneously, presenting itself as a contiguous enterprise. These sets called Horst Waldraff I and Horst Waldraff II will be the object of study of the present research. The post-occupation evaluation included the analysis of the applicability of the Casa Azul Seal, the first Brazilian sustainability certification tool for typical housing projects. Through techniques such as data collection, walkthrough, checklist and structured questionnaires, questions regarding urban quality, design and environmental comfort of the dwellings were investigated, as well as user satisfaction. Through the applied methods it was possible to identify vulnerable points that stand out in the variables focused on the environmental comfort and the urban quality of the dwellings that, besides reflecting on the satisfaction of the user, also reflect in the low applicability of the sustainability actions proposed by the Casa Azul Seal.